Implantación de contabilidad comercial en la asociación de empleados del ilustre municipio de Centinela del Cóndor de la ciudad de Zumbi, periodo enero-marzo del 2013 - Soto Valarezo, Viviana Elizabeth (2014)
The present thesis entitled: "IMPLEMENTATION OF COMMERCIAL ACCOUNTS EMPLOYEES ASSOCIATION OF DISTINGUISHED TOWNSHIP OF CANTON SENTINEL THE SENTINEL OF CONDOR, PERIODO JANUARY-MARCH 2013" was conducted in order to provide input to business enterprises dedicated to this economic activity through the optimization and good management of both material resources, human and financial. In particularly help the ILUSTRE EMPLOYEES ASSOCIATION CITY SENTINEL OF THE CONDOR for the proper performance of the administrative, financial and accounting by implementing commercial accounts. By implementing the Commercial Accounting company under study was achieved to comply with the proposed targets, starting with the structuring of a Plan and Accounts Manual according to the activity carried out by this company, then proceeded to develop the initial inventory of all assets and liabilities, in the same way was designed Daybook were scored in chronological order the operations that occurred in the company once jornallizadas transactions proceeded to mayorizar to prepare the Trial Balance, Cost Sheet and the respective adjustments allowed the generation process results through Income Statement, Statement of Financial Position and Cash Flow. With the completion of this thesis it can be concluded that an accounting system implemented in order to study the association will obtain sufficient information, real and timely so that your managers can improve the economic and financial development of your organization, so it is recommended to use and application.